Melanoma in congenital melanocytic naevi. (4th April 2017) - Kinsler, V.A.; O'Hare, P.; Bulstrode, N.; Calonje, J.E.; Chong, W.K.; Hargrave, D.; Jacques, T.; Lomas, D.; Sebire, N.J.; Slater, O.
Summary: Congenital melanocytic naevi (CMN) are a known risk factor for melanoma, with the greatest risk currently thought to be in childhood. There has been controversy over the years about the incidence of melanoma, and therefore over the clinical management of CMN, due partly to the difficulties of histological diagnosis and partly to publishing bias towards cases of malignancy. Large cohort studies have demonstrated that melanoma risk in childhood is related to the severity of the congenital phenotype. New understanding of the genetics of CMN offers the possibility of improvement in diagnosis of melanoma, identification of those at highest risk, and new treatment options. We review the world literature and our centre's experience over the last 25 years, including the molecular characteristics of melanoma in these patients and new melanoma incidence and outcome data from our prospective cohort. Management strategies are proposed for presentation of suspected melanoma of the skin and the central nervous system in patients with CMN, including use of oral mitogen‐activated protein kinase kinase inhibitors in NRAS ‐mutated tumours. Abstract : What's already known about this topic? Multiple congenital melanocytic naevi (CMN) are the greatest risk factor for paediatric melanoma. Different clinical phenotypes have different risks of malignancy; however, the overall absolute risk for all types of CMN taken together is low. CMN can develop proliferative nodules that can cause diagnostic uncertainty and lead to repeated resections. Histology in patients with CMN is difficult and often requires specialist review. Melanoma in CMN is highly aggressive. What does this study add? In our prospective cohort, the strongest statistical risk factor for all‐site melanoma in childhood is an abnormal screening MRI of the central nervous system (CNS) in the first months of life, and in this group the incidence is 12%. Where melanoma does arise in children with multiple CMN, a primary in the CNS is at least as common as in the skin. CNS melanoma currently has 100% mortality, but oral mitogen‐activated protein kinase kinase inhibition in NRAS ‐mutation mosaic patients may improve symptom control. Management strategies are proposed for the presentation of a possible malignancy in the skin or CNS.